The performance of politics Obama's victory and the democratic struggle for power - Alexander, Jeffrey C., 1947- (New York ; Oxford : Oxford University Press, 2010)
This text develops a new way of looking at democratic struggles for big time power by explaining and analysing the 2008 presidential campaign in the United States.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Presidents -- United States -- Election -- 2008.; Obama, Barack; United States -- Politics and government -- 2001-2009.